2013
DOI: 10.1093/abbs/gms115
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-mediated delivery of siRNA targeting TM4SF4 attenuated liver cancer cell growth <italic>in vitro</italic> and <italic>in vivo</italic>

Abstract: Gene targeting using short interfering RNA (siRNA) has become a common strategy to explore gene function because of its prominent efficacy and specificity. The human transmembrane 4 superfamily member 4 (TM4SF4) was originally identified in intestine and liver as a cell proliferation-related gene. Recently, it showed an increased expression in the hepatocellular carcinoma (HCC) tissues. In this study, we developed an adenoviral vector harboring an effective siRNA targeting TM4SF4 (AdSiTM4SF4) and identified it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
(27 reference statements)
1
11
0
Order By: Relevance
“…TM4SF4 triggered OPN expression by creating a positive feedback autocrine loop with JAK2/STAT3 or focal adhesion kinase (FAK)/STAT3 pathways. Blocking the activity of TM4SF4 using specific antibody and short interfering RNA (siRNA) can be a promising therapeutics against TM4SF4-overexpressing cancer (Wang et al, 2013;Choi et al, 2014).…”
Section: Roles Of Other Tm4sfs In Cancer Development and Progressionmentioning
confidence: 99%
“…TM4SF4 triggered OPN expression by creating a positive feedback autocrine loop with JAK2/STAT3 or focal adhesion kinase (FAK)/STAT3 pathways. Blocking the activity of TM4SF4 using specific antibody and short interfering RNA (siRNA) can be a promising therapeutics against TM4SF4-overexpressing cancer (Wang et al, 2013;Choi et al, 2014).…”
Section: Roles Of Other Tm4sfs In Cancer Development and Progressionmentioning
confidence: 99%
“…Although its structural features imply different functions compared to other members of transmembrane 4 superfamily, there are few studies on TM4SF4 yet except its expression in the liver or intestine [ 18 ]. Overexpression of TM4SF4 is shown in hepatocellular carcinoma and colorectal cancer [ 19 , 20 ] and targeting TM4SF4 with siRNA attenuates the cell growth of hepatocellular carcinoma [ 21 ] which implies TM4SF4 is a potential anti-cancer target. In our previous study, we showed TM4SF4 expression is elevated in non-small cell lung cancer cells (NSCLC) via loss of promoter methylation and confers γ-radiation resistance through activation of the IGF1Rβ/PI3K/AKT/NFκB pathway [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, adenoviral integration events and integration mutations are rare (47,48). Currently, the delivery of siRNA into target tissues for the interference in expression of disease-related specific genes by using adenoviral vectors has yielded satisfactory results (12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…The adenovirus genome is highly homologous with the human genome. Currently, the delivery of siRNA into target tissues for the interference of expression of disease-related specific genes using an adenoviral vector has achieved satisfactory results (11)(12)(13)(14). However, to our knowledge, there is no report of siRNA targeting the PPARg gene aimed at preventing steroidinduced ONFH.…”
Section: Introductionmentioning
confidence: 99%